Calcium phosphate cement as a "barrier-graft" for the treatment of human periodontal intraosseous defects - Rajesh J; Nandakumar K; Varma H; Komath Manoj (Wolters Kluwer Medknow Publications, 2009)
Background : Calcium phosphate cements (CPC) are apparently good candidates for periodontal treatment by virtue of their biocompatibility, mouldability and osteoconductivity. However, the clinical efficacy in this regard has not been established. This study is aimed at the evaluation of the efficacy of a formulation of CPC in healing human periodontal intraosseous defects in comparison with hydroxyapatite ceramic granules. Materials and Methods : In this clinical study, 60 patients with periodontal defects were divided into 2 test groups and 1 control group. The defect sites in the test groups were repaired with CPC and hydroxyapatite ceramic granules (HAG). Debridement alone was given in the control group. The progress was assessed at 3, 6, 9 and 12 months observation intervals through soft tissue parameters (probing depth, attachment level and gingival recession). Results: CPC showed significantly better outcome. Probing depth reduction values of CPC, HAG and Control at 6 months were 5.40 ± 1.43, 3.75 ± 1.71 and 2.90 ± 1.48, and those at 12 months were 6.20 ± 1.80, 4.5 ± 1.91 and 2.95 ± 1.73. Clinical attachment gain values of CPC, HAG and Control at 6 months were 5.15 ± 1.50, 3.45 ± 1.96 and 2.25 ± 1.52, and those at 12 months were 5.80 ± 2.02, 3.55 ± 2.06 and 2.30 ± 1.78, In both cases the P value was < 0.001 showing high significance. The gingival recession over 12 months, for the CPC group is lesser than that in the HAG group and the value for the control group is marginally higher than both. Soft-tissue measurements were appended by postoperative radiographs and surgical re-entry in selected cases. Conclusions: Calcium phosphate cement is found to be significantly better than hydroxyapatite ceramic granules. The material could be considered as a "barrier-graft".